Sustainable Innovation, Digitalization, and Economic Resilience: A Systematic Literature Review on SMEs - Sabil, Sabil; Hakim, Lukman; Lestiningsih, Amin Setio; Widodo, Dwiyatmoko Puji; Hakim, Sugiyah; Sofyanty, Devy (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Digital transformation has become one of the main drivers of sustainable innovation in small and medium-sized enterprises (SMEs), especially in the face of global disruption and the need to adapt to rapid market changes. This study aims to examine the relationship between sustainable innovation, digitalization, and the economic resilience of SMEs, with a focus on how digital transformation strategies can enhance competitiveness while supporting sustainable business practices. Using a systematic literature review approach, this article analyzes relevant scientific publications to identify patterns, trends, and key thematic categories emerging from the current literature. The findings reveal that digital transformation drives new, more adaptive business models, strengthens dynamic capabilities, and enhances SMEs' resilience in facing crises. Additionally, the literature emphasizes that digitalization plays a crucial role in accelerating innovation in products and services oriented toward sustainability, while also opening opportunities for SMEs to access global markets in a more inclusive manner. This research contributes conceptually by offering a synthesis framework on the role of digitalization in sustainable innovation and SME economic resilience, while also providing practical implications for business actors and policymakers in formulating strategies to strengthen SME competitiveness in the digital era. These findings also open up further research opportunities on contextual digital adoption models and mechanisms for implementing sustainable innovation across various industrial sectors.